1999
DOI: 10.1017/s0033291799008995
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and health belief variables associated with frequent attendance in primary care

Abstract: Our findings document the association of psychosocial factors and primary health care use. We suggest that the effective management of mental health problems from a family-based approach may reduce primary health care high use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 45 publications
7
50
0
7
Order By: Relevance
“…10,27,28 One study conducted in the city of Granada, Spain, found that chronic bronchitis was a very common disease among frequent attenders. 27 Al-Windi, by means of questionnaire surveys and computerised medical records, demonstrated that musculoskeletal, cardiopulmonary, and head symptom groups were significantly related to high past and prospective primary care consultation rates. 28 The main difference between the present study and previous ones is related to definitions of frequent attendance.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…10,27,28 One study conducted in the city of Granada, Spain, found that chronic bronchitis was a very common disease among frequent attenders. 27 Al-Windi, by means of questionnaire surveys and computerised medical records, demonstrated that musculoskeletal, cardiopulmonary, and head symptom groups were significantly related to high past and prospective primary care consultation rates. 28 The main difference between the present study and previous ones is related to definitions of frequent attendance.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…They show more family dysfunction [11], and are more likely to be divorced or widowed [7,9]. They are clinically heterogeneous exhibiting higher rates of non disease-specific physical and chronic illness [7,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…They show more family dysfunction [11], and are more likely to be divorced or widowed [7,9]. They are clinically heterogeneous exhibiting higher rates of non disease-specific physical and chronic illness [7,[11][12][13]. Higher rates of FA are found in association with mental illness [11,[14][15][16][17][18][19], the likelihood of FA increasing with anxiety disorder by a factor of 1.14 in a multi-adjusted model [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with a high risk of psychiatric disturbance were excluded. There are indications that these patients perceive symptoms more serious and perceive greater need to consult a GP than patients with a low risk [39]. So, the differences between patients on the one hand, and GPs and practice staff on the other hand, we assessed in our study might be slightly underestimated.…”
Section: Strength and Limitations Of The Studymentioning
confidence: 85%